Responsibility Sharing in International Refugee Law : Towards Common but Differentiated Legal Obligations - Mavropoulou, Elizabeth, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
Achieving a more fair and equitable sharing of refugee protection responsibilities between states has been a perennial challenge of the global refugee regime. The Refugee Convention did not codify a legal obligation of responsibility sharing and as a result any assistance to refugee host states remains voluntary. This responsibility sharing gap has in turn negatively impacted on the quality of refugee protection and on interstate relations by exacerbating existing inequalities undermining the fairness of the international refugee law regime. This book offers a pragmatic yet principled solution to the responsibility sharing gap. It puts down a detailed proposal for the long-resisted UN Protocol on Responsibility Sharing which would codify a light package of responsibility sharing obligations by requiring states to contribute to refugee protection and solutions under a framework of common but differentiated responsibilities based on capabilities. Building on the Global Compact on Refugees and drawing inspiration from international climate change law, the book makes a compelling case for further multilateral law making.